Article can jeopardize good ties between Indonesia, M'sia - Yudhoyono - Borneo Post, (KK) (Borneo Post (kk), 2012)
JAKARTA; Indonesian' President Susiio Bambang Yudhoyono said the article written by former Malaysian Information Minister, Tan Sri Zainuddin Maidin on Indonesia's third President BJ Habibie, was improper and unethical. The article, he said could jeopardize the good ties between Indonesia and Malaysia.